2012
DOI: 10.5039/agraria.v7i4a1915
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação agronômica de genótipos de bananeira no Vale do Rio Siriji, Pernambuco

Abstract: RESUMODevido à necessidade de se incrementar o sistema de produção de banana no Estado de Pernambuco, sobretudo no Vale do Siriji foi instalado, no Município de Vicência, um experimento objetivando avaliar o comportamento de sete genótipos de bananeira (Pacovan Ken, PV 79-34, Japira, Preciosa, ST 12-31, YB 42-03 e YB 42-07) em dois ciclos de produção, utilizando-se o delineamento em blocos ao acaso com quatro repetições e 12 plantas por parcela. Foram avaliadas as características: número de dias entre a primei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
1
1
Order By: Relevance
“…Souza et al [24] evaluating the growth and the production of genotypes of banana trees in subtropical climate, they verified that Grande Naine presented 154 days between the flowering and harvesting of the bunch. Silva et al [25] they observed 131 days between the flowering and harvest for the Pacovan Ken banana tree in the Valley Siriji River, Pernambuco, being later than this study, maybe the agroecological management has influenced precocity.…”
Section: Vegetative Phasecontrasting
confidence: 53%
“…Souza et al [24] evaluating the growth and the production of genotypes of banana trees in subtropical climate, they verified that Grande Naine presented 154 days between the flowering and harvesting of the bunch. Silva et al [25] they observed 131 days between the flowering and harvest for the Pacovan Ken banana tree in the Valley Siriji River, Pernambuco, being later than this study, maybe the agroecological management has influenced precocity.…”
Section: Vegetative Phasecontrasting
confidence: 53%
“…The species Hancornia speciosa Gomes, popularly known as 'Mangabeira', is a native fruitful tree of the Brazilian Cerrado, belonging to Apocynaceae, and is widely distributed throughout the country, from Amapá to the state of São Paulo (Silva Junior, Xavier, Silva Lédo, Santos Musser, & Silva Lédo, 2007). Among the attractive characteristics of the species are its fruits that, due to its pleasant flavor, stimulate fresh consumption and can also be used in the production of syrups, juices, candy, ice cream Acta Scientiarum.…”
Section: Introductionmentioning
confidence: 99%